SENSEI: Direct-Detection Results on sub-GeV Dark Matter from a New Skipper CCD - Barak, Liron; Bloch, Itay M.; Cababie, Mariano Ruben; Cancelo, Gustavo Indalecio; Chaplinsky, Luke; Chierchie, Fernando; Crisler, Michael; Drlica Wagner, Alex; Essig, Rouven; Estrada, Juan; Etzion, Erez; Fernández Moroni, Guillermo; et al. (American Physical Society, 2020)
Fil: Barak, Liron. Universitat Tel Aviv; Israel